$n$-Points Inequalities of Hermite-Hadamard Type for $h$-Convex Functions on Linear Spaces - Dragomir, S. S. (Armenian Journal of Mathematics, 2016)
Some $n$-points inequalities of Hermite-Hadamard type for $h$-convex functions defined on convex subsets in real or complex linear spaces are given. Applications for norm inequalities are provided as well.